Innovations in the publishing industry and new forms of scientific production - Madrigal-Torres, Rosalba; Madrigal-Torres, Berta (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The challenges of digitization in the production of knowledge in the social sciences and humanities. The objective was to analyze the evolution of the book, from the clay to the innovation of the computer that modifies the electronic format, the state of the art is a qualitative and interpretative documentary sample of the possibilities and limitations on the new options to produce knowledge. Among the conclusions, it is highlighted that the state of the art is a qualitative documentary research methodology of a critical interpretive nature to review the formats of the book, the obstacles faced by researchers for publishing.